ANALISIS ELECTRONIC WORD OF MOUTH PADA PENGGUNA APLIKASI SHOPEE DI KOTA SANGATTA - Andi Mursalin (Tinta Nusantara 2018 Vol.1, 2022)
This study aims to analyze electronic word of mouth on Shopee application users in Sangatta. The data in this study is a descriptive study. The population in this study were all Shopee application users in Sangatta, the sampling technique used was purposive sampling and a sample of 5 respondents was obtained. Methods of data collection using observation techniques, interviews and documentation. Based on the results of research and discussions that have been carried out regarding electronic word of mouth (e-WOM) on Shopee application users in Sangatta, Shopee application users in Sangatta in conducting e-WOM in the application are based on several supporting indicators such as Intensity, Positive Valence, Negative Valence and Content. These four things are important factors in the e-WOM process that occurs in Shopee application users, especially in Sangatta. From this it can be concluded that the motive of application users doing e-WOM on the Shopee application is to seek information on the products they will buy by interacting with other users and considering the results of reviews that have been written by previous buyers by paying attention to the positive or negative of the quality, variety and price of the products they will buy on the Shopee application.